Teacher’s Perceptions Of The Implementation Of The Pancasila Student Profile In The Kurikulum Merdeka - Sutisnawati, Astri; Marini, Arita; Zakiah, Linda (Universitas Pakuan, 2024)
The Pancasila Student Profile is the vision and mission of the Ministry of Education and Culture Number 22 of 2020 as the embodiment of lifelong students who have global competence and act in accordance with the values contained in Pancasila. This research aims to determine the level of student perception of the Pancasila Student Profile in the independent curriculum. The subjects of this research were 20 elementary school teachers who had implemented the Kurikulum Merdeka in Warudoyong District, Sukabumi City. The data analysis technique uses descriptive statistics, while the data collection technique uses questionnaires and interviews. The results of the research show that the level of perception of elementary school teachers who have implemented an Kurikulum Merdekafor 2 years gave a positive response.